Readiness to Learn Culinary Practices at Universities in the Digital Era of Industry 4.0 - Tangkere, Telly F S (International Journal of Information Technology and Education, 2023)
This study aims to identify and analyze the readiness of learning culinary practices at universities in the digital industry 4.0 era. The digital industry 4.0 era has had a significant impact on various sectors, including education and the culinary industry. As part of culinary education, learning about culinary practices needs to adapt to technological developments and current trends. This research will involve the PKK Department of Manado State University as a research location and focus on culinary education programs. The research method used is a survey and structured interviews. A survey will be conducted to collect data on available digital infrastructure, human resources involved in teaching culinary practices, and the technological knowledge and skills possessed by teachers and students. Interviews will be conducted with teaching staff, students, and representatives from the culinary industry to gain deeper insight into the challenges and opportunities faced in learning culinary practices in the digital industry 4.0 era. The collected data will be analyzed qualitatively using the thematic analysis method. The results of this study are expected to provide a better understanding of the readiness of learning culinary practices at universities in the digital industry 4.0 era. It is hoped that the findings of this study can provide valuable information for universities and other culinary education institutions to improve the curriculum and infrastructure for teaching culinary practice. This research can also provide recommendations for the culinary industry to adapt to changes that occur in the digital industry 4.0 era and prepare graduates with skills relevant to current industry demands.